(untitled) (Herald of Journalism, 2020)
This research presents the results of a sociological study on the media behaviour of the adult population of Kazakhstan viewers of TV «Khabar» in the context of the issue of worldview orientations in the digital age. The aim of the research is to determine the specifics of media consumption of digital technologies of the population of Kazakhstan, as well as to identify media preferences of the adult population. The main tasks of our empirical research are firstly to determine the mechanism of access to the main technical means of communication and digital information channels, and secondly to determine the media behaviour of active users of digital sources. The research methodology is based on quantitative and qualitative methods. The results of the study show a segmentation of the Kazakh audience in terms of usage of digital channels, in terms of information consumption and in terms of media preferences. All regions of the country can be divided into two groups according to the dominant type of television connection into areas where rural population prevails and into areas with a higher level of urbanization. The analysis shows that digital television is being introduced in all areas, with mobile Internet having begun to compete with wired Internet. The identification of media behavior of the adult population of Kazakhstan by television viewers of the Khabar channel in the focus of development and modernization of the digital era determines the practical and scientific significance of this empirical study. The research methodology is based on quantitative and qualitative methods: interviewing the middle of the target group and working in focus groups. The results of the study show that the segmentation of the Kazakhstani audience of digital information channels by style of consumption and the characteristics of the media preferences of the audience of the Khabar TV channel differ. The results of the study can be used in applied work in on social journalism.